THE INFLUENCE OF SELF-CONTROL, OVERCONFIDENCE & FINANCIAL LITERACY ON INVESTMENT DECISIONS OF HIGH RISK ASSETS AMONG THE MILLENNIAL GENERATION AND GENERATION Z - Suprapto, Yandi; Joycelyn; Wisnu Yuwono (STIE PGRI Dewantara Jombang, 2025)
This research is aimed to perform an investigation regarding the capability of financial literacy, including overconfidence bias and self-control proceed a significant influence on shaping Gen Z and Millennials’ decision to invest. Furthermore, the research also examines how risk tolerance mediating role in the relationship between independent-dependent variables. By employing quantitative approach, utilizing PLS-SEM modelling, the research gained data which is derived from 168 active investors in the capital market of Indonesia. The findings shown the significant influence of financial literacy, self-control, and overconfidence in shaping risk tolerance, which also turns out as a bridge towards the decision of individuals to invest. In this context, financial literacy highly encourages higher overconfidence distorts the perception of risk, well-examined risk taking, and self-control which able to foster such impulsive actions, which further shape the decisions of investment choices. The findings also offers such major insights regarding young investors’ behaviour in the capital market and underlines the requirement to utilize an effective and well-targeted financial education and training of behavioural finance. Those results might be applicable for further literatures looking forward in the development of these theoretical models for further financial professionals, purposed in showing more support to client in investigating the emerging landscape of investment.